The Effect of Leadership, Motivation and Job Satisfaction on Organizational Commitment - Muh. Yusuf; M. Risal; Srisapta Srisapta (Universitas Negeri Makassar, 2021)
Public sector organizations or government organizations are actually pioneers in advancing a region. Success in advancing an area can be seen from how well individuals are in their commitment to the organization. This study aims to determine the effect of leadership, motivation and job satisfaction on organizational commitment at echelon 2, 3, and 4 in the Luwu Regency Regional Work Unit (SKPD) with a sample of 87. This study concludes that leadership, motivation and job satisfaction have a significant effect. either partially or simultaneously.